CONCEPT OF AGRICULTURAL ACTIVITY AND THE WORK BEING IMPLEMENTED TO DEVELOP THIS INDUSTRY IN OUR COUNTRY - Esbergenova Svetlana Xojakmetovna (Scholar Express Journal, 2021)
It is known that production in the agricultural sector is often associated with land. Relationships related to land ownership, disposal and use and development are called agrarian relations. The peculiarities of agricultural production are directly related to economic laws and natural laws, because production in the agricultural sector is directly related to living things - land, plants, livestock. In this case, the land is mainly the object of labor (object) and the main means of production, the object of economic management, and if a good relationship is good, its productivity will be good. This article provides information on the concept of agricultural activity and the work being done to develop this sector in our country.
Keywords: Agro-industry; agrarian activity; new projects; development